Asymptomatic carriage rates and case fatality of SARS-CoV-2 infection in residents and staff in Irish nursing homes. (28th September 2020) - Kennelly, Sean P; Dyer, Adam H; Noonan, Claire; Martin, Ruth; Kennelly, Siobhan M; Martin, Alan; O'Neill, Desmond; Fallon, Aoife
Abstract: Background: SARS-CoV-2 has disproportionately affected nursing homes (NH). In Ireland, the first NH case COVID-19 occurred on 16 March 2020. A national point-prevalence testing programme of all NH residents and staff took place (18 April 2020 to 5 May 2020). Aims: to examine characteristics of NHs across three Irish Community Health Organisations, proportions with COVID-19 outbreaks, staff and resident infection rates symptom profile and resident case fatality. Methods: in total, 45 NHs surveyed, requesting details on occupancy, size, COVID-19 outbreak, outbreak timing, total symptomatic/asymptomatic cases and outcomes for residents from 29 February 2020 to 22 May 2020. Results: surveys were returned from 62.2% (28/45) of NHs (2, 043 residents, 2, 303 beds). Three-quarters (21/28) had COVID-19 outbreaks (1, 741 residents, 1, 972 beds). Median time from first COVID-19 case in Ireland to first case in these NHs was 27.0 days. Resident incidence was 43.9% (764/1, 741)—40.8% (710/1, 741) laboratory confirmed, with 27.2% (193/710) asymptomatic and 3.1% (54/1, 741) clinically suspected. Resident case fatality was 27.6% (211/764) for combined laboratory-confirmed/clinically suspected COVID-19. Similar proportions of residents in NHs with 'early-stage' (<28 days) versus 'later-stage' outbreaks developed COVID-19. Lower proportions of residents in 'early' outbreak NHs had recovered compared with those with 'late' outbreaks (37.4 versus 61.7%; χ 2  = 56.9, P  < 0.001). Of 395 NH staff across 12 sites with confirmed COVID-19, 24.7% (99/398) were asymptomatic. There was a significant correlation between the proportion of staff with symptomatic COVID-19 and resident numbers with confirmed/suspected COVID-19 (Spearman's rho = 0.81, P  < 0.001). Conclusion: this study demonstrates the significant impact of COVID-19 on the NH sector. Systematic point-prevalence testing is necessary to reduce risk of transmission from asymptomatic carriers and manage outbreaks in this setting.